Utilization of acid pre-treated coconut dregs as a substrate for production of detergent compatible lipase by Bacillus stratosphericus - Zin, Nur Bainun Mohd; Yusof, Busyra Mohamad; Oslan, Siti Nurbaya; Wasoh, Helmi; Joo, Shun Tan; Ariff, Arbakariya B.; Halim, Murni (Springer Open, 2017)
In recent years, many efforts have been directed to explore the methods to reduce the production costs of industrial lipase by improving the yield and the use of low-cost agricultural wastes. Coconut dregs, which is a lignocellulosic by-product from coconut oil and milk processing plants, is rich in cellulose (36%) and crude fat (9%). A newly isolated Bacillus stratosphericus has been demonstrated to perform cellulose hydrolysis on coconut dregs producing fermentable sugars. The highest extracellular lipase activity of 140 U/mL has been achieved in submerged fermentation with acid pre-treated coconut dregs. The lipase was found to be active over a wide range of temperatures and pHs. The activity of lipase can be generally increased by the presence of detergent ingredients such as Tween-80, cetyltrimethylammonium bromide, hydrogen peroxide and phosphate per sulphate. The great compatibility of lipase in commercial detergents has also underlined its potential as an additive ingredient in biodetergent formulations.